Index insurance for managing climate-related agricultural risk: toward a strategic research agenda - Nicola, F. de; Hill, Ruth Vargas; Carter, M.; Choularton, R.; Hansen, James; Osgood, D. (International Food Policy Research Institute, 2011)
In October 2011, the CGIAR program on Climate Change, Agriculture and Food Security (CCAFS) and the Index Insurance Innovation Initiative (I4) organized a joint workshop hosted by the International Food Policy Research Institute (IFPRI). The workshop was designed to identify and address issues surrounding index‐based insurance for smallholder farmers and the rural poor in the developing world. Emphasis was placed on identifying key areas of research and learning for the academic and policy community to pursue. The workshop took as its starting point the idea that there is large potential in using indices to insure smallholder farmers. However, in practice, the costs of providing and scaling up index insurance have not been insubstantial. In view of this potential and these constraints, workshop participants identified key areas of research and learning aimed at increasing the benefits of index‐based insurance to smallholder farmers and the rural poor in the developing world. This report summarizes the findings of the two‐day workshop.